Molecular Weight Dependence of Synthetic Glycopolymers on Flocculation and Dewatering of Fine Particles - Lu, Han (Langmuir : the ACS journal of surfaces and colloids, 2016)
In this study, poly(2-lactobionamidoethyl methacrylamide) of various molecular weights (MWs) was synthesized using conventional free-radical polymerization. The effect of MW and polymer dosage on the settling rate of kaolin particles, turbidity of the supernatant, mud-line position, and solid content was investigated to determine the flocculation performance. The interaction forces, polymer conformation, particle sizes, and MWs were determined using several techniques, including surface forces apparatus, atomic force microscopy (AFM), dynamic light scattering, and gel permeation chromatography. Our results reveal that the initial settling rate of kaolin particles and the clarity of supernatants increase with increasing MW of the glycopolymers. Surface force measurements and AFM imaging of the adsorbed polymer surfaces show strong polymer-particle adhesion and bridging attraction between the glycopolymers and clay surfaces, which increase with increasing MW of the glycopolymer. The strengthened bridging attraction with the polymer MW is attributed to the formation of stronger adhesion (e.g., via hydrogen bonding) between the fine particles and the abundant hydroxyl groups in the glycopolymers of higher MW, thus contributing to enhanced flocculation behaviors. Our results provide new insights into the development of eco-friendly polymer flocculants based on glycopolymers for an efficient solid-liquid separation in tailing treatment and into the fundamental understanding of associated intermolecular interactions and flocculation mechanisms